Losses, Efficiency and Thermal Behavior of the Synchronous Motors with Different PM Materials - Peter Sekerak; Valeria Hrabovcova; Matus Onufer; Pavol Rafajdus; Lukas Kalamen (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with losses, efficiency and thermal behavior of the synchronous machines with different permanent magnet (PM) materials. Three PMSM are presented in this paper: First, the PMSM with NdFeB PM, which is really constructed. Second, the NdFeB was replaced by ferrites PM. Third, the new design of synchronous motor with ferrites is presented. The volume of PM and the whole size are increased to keep the same power output. Equivalent circuit parameters, EMF, V-curves, losses, efficiency and thermal behavior of all three machines are investigated and compared.